Sobre as dúvidas que as autoridades na América portuguesa ofereciam ao centro da monarquia portuguesa. Uma reflexão sobre a prática e a comunicação políticas (c. 1600-c. 1750) - Roberta Stumpf (Les Cahiers de Framespa)
This article analyses the sources produced in the seventeenth and eighteenth centuries by authorities in Portuguese America who have sent their doubts to the Overseas Council and to the Portuguese Crown on different aspects / issues related to the administration. Such uncertainties convey significant dimensions of political communication between the two segments and, after all, a component of negotiation between them. Existing administrative practices and the use of doubt vested the royal agents with argumentative tools that broadened their power of interlocution. From the analysis of a number of cases, we can observe the different motivations of the officers who were behind this communication such as fear of making mistakes and the deliberate intention of resisting orders.